Irrigation Advisory Service and Performance Indicators in Baixo Acaraú Irrigation District, Brazil†. (3rd September 2015) - Corcoles, J. I.; Frizzone, J. A.; Lima, S. C. R. V.; Mateos, L.; Neale, C. M. U.; Snyder, R. L.; Souza, F.
Abstract: Several decision support systems have been developed and many of them are focused on efficient use of water and energy resources. These include the Irrigation Advisory Service, combined with the use of benchmarking techniques and energy audits. In Brazil, the pioneer project called the Irrigation Advisory Service has been developed in Baixo Acaraú irrigation district, located in the north‐east of Brazil. The main goal of the project is to transfer information about irrigation to farmers. The aim of this paper is to present the results of the Irrigation Advisory Service activities in Baixo Acaraú irrigation district, during the 2011, 2012 and 2013 irrigation seasons. Moreover, the results from the estimation of several performance indicators and from energy: audits carried out are shown as a complementary activity developed by the Irrigation Advisory Service. At the beginning of the irrigation season, on‐field emission of uniformity was close to 67%. During the following evaluations, after recommendations of the Irrigation Advisory Service about the necessity of corrections to the systems, emission of uniformity reached 85%. With regard to the use of performance indicators, some problems relating to maintenance of equipment were noted, resulting in malfunctioning pumps. Copyright © 2015 John Wiley & Sons, Ltd.